Interaction Between Intrinsic Renal Cells and Immune Cells in the Progression of Acute Kidney Injury - Deng, Junhui; Wu, Zhifen; He, Yun; Lin, Lirong; Tan, Wei; Yang, Jurong (Frontiers in Medicine, 2022)
A growing number of studies have confirmed that immune cells play various key roles in the pathophysiology of acute kidney injury (AKI) development. After the resident immune cells and intrinsic renal cells are damaged by ischemia and hypoxia, drugs and toxins, more immune cells will be recruited to infiltrate through the release of chemokines, while the intrinsic cells promote macrophage polarity conversion, and the immune cells will promote various programmed deaths, phenotypic conversion and cycle arrest of the intrinsic cells, ultimately leading to renal impairment and fibrosis. In the complex and dynamic immune microenvironment of AKI, the bidirectional interaction between immune cells and intrinsic renal cells affects the prognosis of the kidney and the progression of fibrosis, and determines the ultimate fate of the kidney.